Information systems validation using formal models - Azadeh Sarram; Ali Harounabadi (Management Science Letters)
During the past few years, there has been growing interest to use unified modeling language (UML) to consider the functional requirements. However, lacking a tool to detect the accuracy and the logic of diagrams in this language makes a formal model indispensable. In this study, conversion of primary UML model of a system to a colored Petri net has been accomplished in order to examine the precision of the model. For this purpose, first the definition of priority and implementation tags for UML activity diagram are provided; then it is turned into colored Petri net. Second, the proposed model provides translated tags in terms of net transitions and some monitoring are used to control the system characteristics. Finally, an executable model of UML activity diagram is provided so that the designer could simulate the model by using the simulation results to detect and to refine the problems of the model. In addition, by checking the results, we find out the proposed method enhances authenticity and accuracy of early models and the ratio of system validation increases compared with previous methods.